Analyzing genetic diversity and correlation of statice (Limonium sinuatum L.) varieties in Lam Dong using RAPD-PCR technique - Thuc, Le Van; Hung, Le Duc; Linh, Le Thi Thuy; Dien, Han Huynh; Thy, Le Thi Bich; Que, Tran; Lan Anh, Hoang Le; Tung, Hoang Thanh; Nhut, Duong Tan (Vietnam Journal of Biotechnology, 2021)
In this study, 12 varieties of statice (Limonium sinuatum L.) were collected from famous flower growing areas (Van Thanh, Thai Phien, Da Thien, Ha Dong and Trai Mat) in Lam Dong. Young foliage of flowering cultivars after 45 days of planting at the experimental site was collected for DNA extraction and genetic correlation analysis using RAPD with 13 random primers. Results showed that out of 145 RAPD bands, there were 133 polymorphic bands (91.72%) and 12 monomorphic bands (8.28%). Of which, the OPB-03 primer has the highest number of amplifiers, which is 17 bands (with 16 polymorphic bands); the genetic difference coefficients ranged from 0.30 to 0.90, mean 0.55. The results of the genetic sequence analysis using NTSYSpc 2.1 showed that 12 varieties of statice were divided into 4 groups: group I consisting of 3 varieties (rose pink, dark pink and pure magenta); Group II including 2 varieties (blue violet and new violet); Group III including 6 varieties (light pink, old violet, new white, old white, light yellow and light violet); Group IV consisting only 1 variety (cadimi yellow). This result is an important database in the conservation of statice genetic resources, as well as provides the necessary information to select mutant breeding of this species in the coming time.